THE IMPACT OF THE BUSINESS SECTOR ON CHILDREN’S RIGHTS IN SERBIA - Krstic, Natasa T; Nešić, Sandra (The European Journal of Applied Economics, 2020)
The business sector has a strong direct and indirect impact on children, at the workplace, on the marketplace, in the community and through the supply chain, where risks arise in terms of endangering children and their rights. This paper aims to provide new evidence of the impact of the business sector on children’s rights in Serbia. The analysis of the impact of the Serbian business sector on children's rights was carried out through cabinet research of three sectors identified as a priority based on their influence on the economy and children's rights – ICT, food and agribusiness and financial sector. After interviews with managers responsible for corporate social responsibility in the leading companies from these sectors, their potential impact on children's rights has been mapped together with sectoral risks, while opportunities for shared-value engagement between businesses and organizations and institutions supporting children and their rights were extracted. Our research suggests that shared value in the context of the promotion of children's rights goes far beyond traditional corporate philanthropy and audits how core business operations, assets and practices, advocacy initiatives, skills and know-how can support children's rights in achieving Sustainable Development Goals.
Keywords: Business Principles and Children’s Rights; Corporate Social Responsibility; Shared Value; Serbia.